Tenses in Vergil's Aeneid : narrative style and structure - Adema, Suzanne Maria, 1978- (Amsterdam Studies in Classical Philology, 2019)
The narrative style of the Aeneid suggests immediacy and involves the reader, while at the same time both narrator and reader know what the outcomes of the story will be. In 'Tenses in Vergil's Aeneid: Narrative Style and Structure' , Suzanne Adema investigates the role of the Latin tenses in this presentational style. Adema presents a framework to analyze and describe the use of tenses in Latin narrative texts from a linguistic and narratological point of view. The framework concerns the temporal relations between a narrator and the states of affairs in his story on the sentence level, discourse modes on the global text level and narrative progression on the level of narrative and descriptive sequences.